The Molecular Effects of BDNF Synthesis on Skeletal Muscle: A Mini-Review - Rentería, I.; García-Suárez, P. C.; Fry, A. C.; Moncada-Jiménez, J.; Machado-Parra, J. P.; Antunes, B. M.; Jiménez-Maldonado, A. (Frontiers in Physiology, 2022)
The brain-derived neurotrophic factor (BDNF) is a member of the nerve growth factor family which is generated mainly by the brain. Its main role involve synaptic modulation, neurogenesis, neuron survival, immune regulation, myocardial contraction, and angiogenesis in the brain. Together with the encephalon, some peripheral tissues synthesize BDNF like skeletal muscle. On this tissue, this neurotrophin participates on cellular mechanisms related to muscle function maintenance and plasticity as reported on recent scientific works. Moreover, during exercise stimuli the BDNF contributes directly to strengthening neuromuscular junctions, muscle regeneration, insulin-regulated glucose uptake and β-oxidation processes in muscle tissue. Given its vital relevance on many physiological mechanisms, the current mini-review focuses on discussing up-to-date knowledge about BDNF production in skeletal muscle and how this neurotrophin impacts skeletal muscle biology.